2009
DOI: 10.1097/opx.0b013e3181a7b0ff
|View full text |Cite
|
Sign up to set email alerts
|

Course of Development of Global Hyperacuity Over Lifespan

Abstract: Purpose Global visual integration is fundamental to shape and face recognition. While the maturation of local visual function, such as resolution acuity, has been well documented, less is known about the changes in global visual function during development and with aging. Methods Two hundred thirty-six normal subjects, ranging in age from 0.25 to 78 years old, participated the study. Global hyperacuity (detection threshold for radial deformation) was obtained from 300 eyes using either a computerized testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
37
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 37 publications
5
37
2
Order By: Relevance
“…11,[13][14][15] The radial deformation task has been adapted to a forced-choice preferential looking paradigm and used to document the rapid improvement of hyperacuity during the first year of life. 16,17 The rate of radial deformation hyperacuity maturation is similar to that reported with more traditional hyperacuity stimuli. 16 Adults with strabismic amblyopia have severe deficits in radial deformation hyperacuity in the amblyopic eye compared to the fellow eye.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…11,[13][14][15] The radial deformation task has been adapted to a forced-choice preferential looking paradigm and used to document the rapid improvement of hyperacuity during the first year of life. 16,17 The rate of radial deformation hyperacuity maturation is similar to that reported with more traditional hyperacuity stimuli. 16 Adults with strabismic amblyopia have severe deficits in radial deformation hyperacuity in the amblyopic eye compared to the fellow eye.…”
supporting
confidence: 65%
“…26,27 Wang et al 17 report the development and course of global hyperacuity from infancy to aging. The normative data presented in this study for early childhood through teenage years agrees well with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual functions, such as hyperacuity, continue to develop until 21 years of age. 20 Although this has been attributed to refinement of neural circuitry at the cortical level, it is possible that ongoing retinal development during this period also may be contributing to this process.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18,19 In contrast, it has been shown that visual functions increase until adulthood, which has been attributed to maturation of the visual cortex. 20 The aim of this study was to determine the developmental time course and trajectories for each retinal layer at the fovea and define the contribution of each retinal layer to the development of normal vision in full-term infants and young children using HH-SDOCT.…”
mentioning
confidence: 99%